IMPLEMENTASI DAN PROBLEMATIKA PROGRAM MERDEKA BELAJAR DAN KAMPUS MERDEKA PADA LEMBAGA PENDIDIKAN ISLAM - Hidayati, Helma; Ansary, Hafiz; Ajahari, Ajahari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the demands of implementing the Merdeka Belajar–Kampus Merdeka (MBKM) program in improving the quality of education that is flexible, adaptive, and student-centered, particularly in Islamic educational institutions that integrate scientific knowledge with Islamic values. However, its implementation still faces various challenges, such as limitations in human resources, inadequate understanding of policies, and insufficient facilities and infrastructure. This study aims to describe the implementation of MBKM, identify the challenges encountered, and formulate relevant solutions. The method used is qualitative research with a library research approach, involving the analysis of secondary data from books, journals, and scientific articles using content analysis techniques. The results indicate that the implementation of MBKM has been carried out through curriculum adjustments based on Outcome-Based Education (OBE) in higher education and the application of the Merdeka Curriculum with a differentiated approach in madrasahs, although it has not been fully optimized. The challenges include difficulties in integrating Islamic values, limited understanding among educators, unequal access to collaboration, and minimal facility support. Therefore, improving educators’ competencies, strengthening collaboration, and enhancing policy and infrastructural support are necessary for more effective implementation.